Sowing date and fungicide application in the agronomic performance of oleaginous brassica for the biodiesel production - Ometto Zorzenoni, Thiago; Pacheco de Andrade, Aguinaldo; Riyuiti Higashibara, Leandro; Cajamarca, Fábio Antonio; Shigueru Okumura, Ricardo; Cavenaghi Prete, Cássio (Revista Ceres, 2025)
This work aims to evaluate the agronomic performance of crambe and juncea canola, sowed in the summer and winter season intervals with and without fungicide application. The cultivars used were FMS Brilhante and Terola 25A85 for crambe and juncea canola, respectively. The experimental design was randomized blocks in split plots, in which the plots were sowing dates 15th May (E1), 1st June (E2) and 15th June 2014 (E3), and the split plots with and without aboveground part with fungicide (trifloxystrobin 150 g L-1 + prothioconazole 175 g L-1). The evaluated variables were plant height, thousand seed weight, seed yield, oil content and oil yield. The sowing dates had had influence only on plant height for crambe, while juncea canola had a significant effect on plant height, seed yield and oil yield. The fungicide application gave higher seed yield for crambe and for juncea canola, higher thousand seed weight, seed yield and oil yield. With the production technologies adopted for the growth of these two brassicas, it is necessary to obtain higher yields of seeds and oil, to enable the commercial exploration in the interval between the summer and winter off-season in the Northern region of Paraná state, Brazil.